Potent in vitro collagen biosynthesis stimulating and antioxidant activities of edible mushroom Volvariella volvacea aqueous extract - Warintorn Ruksiriwanich (2018)
Beside Thai herbs and spices, several mushrooms are used in Thai cuisine such as straw mushrooom(Volvariella volvacea) in Tom Yam Kung. Objective: To investigate the in vitro collagen biosynthesis stimulating and antioxidant activities of edible mushrooms which are common use as Thai food ingredient including V. volvacea collected from northern Thailand. Methods: The 11 selected mushrooms were extracted by three extraction methods including the hot (HW) and sonicated (SW) aqueous and the macerated ethanolic (ME) processes. These extracts were tested for antioxidative activity (including DPPH radical scavenging, metal chelating and lipid peroxidation) and in vitro collagen biosynthesis stimulating activities. Results: The sonicated aqueous extracts of V. volvacea (VV SW) not only showed the highest total phenolic (6.68 mg GAE) and polysaccharide contents (0.069 mg GLU) but also gave the highest DPPH radical scavenging, lipid peroxidation inhibition and collagen biosynthesis stimulating activities with the relative amount of the collagen biosynthesis stimulation of 146.77±13.20% of negative control which was significantly higher than standard ascorbic acid at about 1.14 times. Conclusion: This present study has suggested the sonicated aqueous extracts of V. volvacea to be developed as a functional food or cosmeceutical product with the potent in vitro collagen biosynthesis stimulating and antioxidant activities which can be promoted the traditional ingredient for Thai cuisine recipes as well.